2008
DOI: 10.1063/1.2837659
|View full text |Cite
|
Sign up to set email alerts
|

Dependence of noise in magnetic tunnel junction sensors on annealing field and temperature

Abstract: The minimum detectable field of magnetoresistive sensors is limited by their intrinsic noise. Magnetization fluctuations are one of the crucial noise sources and are related to the magnetization alignment at the antiferromagnetic-ferromagnetic interface. In this study, we investigated the low frequency noise of magnetic tunnel junctions ͑MTJs͒ annealed in the temperature range from 265 to 305°C and magnetic fields up to 7 T, either in helium or hydrogen environments. Our results indicate that the magnetic fluc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(11 citation statements)
references
References 12 publications
1
10
0
Order By: Relevance
“…The magnetic noise in this sensor is significantly reduced by our annealing process similar to results presented in Ref. 16. Fig.…”
Section: Fabrication Of Magnetoresistive Sensorsupporting
confidence: 73%
See 2 more Smart Citations
“…The magnetic noise in this sensor is significantly reduced by our annealing process similar to results presented in Ref. 16. Fig.…”
Section: Fabrication Of Magnetoresistive Sensorsupporting
confidence: 73%
“…The sensor voltage and preamplifier bias are supplied by batteries to minimize noise. The MTJ sensor bridge was annealed at 265°C under a 7 T magnetic field for 15 min in a hydrogen environment which have been demonstrated to reduce the noise level of the MTJs at low frequency [16].…”
Section: Fabrication Of Magnetoresistive Sensormentioning
confidence: 99%
See 1 more Smart Citation
“…The nonmagnetic 1/f noise from the barrier can be substantially reduced by thermal annealing. 12,13 The magnetic 1/f noise is the dominant noise source in MTJs. Reducing the magnetic noise is of importance to improve the field detectivity in MTJ (sensor) devices.…”
mentioning
confidence: 99%
“…It has been shown that low frequency magnetic noise in TMR sensors can be reduced by the application of a hard axis bias field 6 and annealing in a high magnetic field. 9 In this work, we developed a TMR sensor with perpendicular anisotropy in the sensing layer and we used the voltage-induced anisotropy modulation as an efficient means of reducing magnetic noise.…”
mentioning
confidence: 99%